2022
DOI: 10.1002/pen.26221
|View full text |Cite
|
Sign up to set email alerts
|

Modification of nanofibrous scaffolds to mimic extracellular matrix in physical and chemical structuring

Abstract: Regulating the surface chemistry and topography of the scaffolds is an effective way to improve the scaffolds' biocompatibility. A nanofibrous scaffold with topographical and chemical biomimicry to ECM was developed in this study. In which, PCL nanofibrous scaffold was employed as a substrate which was shish-kebab structured first to provide the topographical similarity with ECM and then coated with polydopamine and arginylglycylaspartic acid (RGD) to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…These results indicated that the PDA and PDA/RGD coatings can modify the hydrophobicity of pristine PCL fibers due to the presence of the carboxyl and amine groups provided by PDA and RGD. In a previous study, researchers demonstrated that grafting RGD onto PDA-coated PCL fibers resulted in better wettability than the PDAcoated fibers [32,34]. Similarly, our results suggest that the PDA/RGD copolymerization coating method is a simple procedure that increases wettability in only one step.…”
Section: Water Contact Angle Measurementsupporting
confidence: 80%
“…These results indicated that the PDA and PDA/RGD coatings can modify the hydrophobicity of pristine PCL fibers due to the presence of the carboxyl and amine groups provided by PDA and RGD. In a previous study, researchers demonstrated that grafting RGD onto PDA-coated PCL fibers resulted in better wettability than the PDAcoated fibers [32,34]. Similarly, our results suggest that the PDA/RGD copolymerization coating method is a simple procedure that increases wettability in only one step.…”
Section: Water Contact Angle Measurementsupporting
confidence: 80%
“…[10,11] Further, various fabrication techniques were employed, including 3D printing, the sol-gel process, lyophilization, electrospinning, porogen leaching, and gas foaming, among others. [6,[11][12][13] Nevertheless, existing scaffolds are still far from being adopted for successful clinical usage, as many requirements for bone regeneration contradict each other. [14] For example, high porosity is essential for nutrients and cell diffusivity; however, on the downside, it leads to poor mechanical properties.…”
Section: Introductionmentioning
confidence: 99%